determinant of psychophysiological state of sportsmen of high qualification with different emotional characteristics - Korobeynikova L.G (Kharkov National Pedagogical University, 2011)
The purpose of the work - to study the determinants of psycho-physiological state of sportsmen of high qualification with different emotional characteristics. In experiment took part 19 highly skilled athletes involved in the Greco-Roman wrestling. The survey was carried out using a hardware-software complex psychodiagnostic "Multipsihometr-05. Determined by the emotional background of athletes according to the method A. Rukavishnikova features of visual perception and perceptual speed.